Impact of atrial flow regulator implantation on survival in patients with heart failure with reduced and preserved ejection fraction: a post-hoc analysis of the PRELIEVE study. (3rd October 2022) - Lauder, L; Bergmann, M; Paitazoglou, C; Ozdemir, R; Iliadis, C; Bartunek, J; Lauten, A; Keller, T; Weber, S; Sievert, H; Anker, S D; Mahfoud, F
Abstract: Purpose: This analysis aims to assess the theoretical impact of atrial flow regulator implantation on mortality by comparing the observed survival rate with the median predicted probability for one-year survival. Methods: The prospective, multicentre, open-label, non-randomised PRELIEVE study assessed the safety and efficacy of the atrial flow regulator in patients with symptomatic HFrEF (left ventricular ejection fraction (LVEF) ≥15% and <40%) or HFpEF (LVEF ≥40% and <70%) and elevated PCWP (≥15mmHg at rest or ≥25mmHg during exercise). In this analysis, after the first 60 patients completed twelve months of follow-up, the theoretical impact of atrial flow regulator implantation on survival was assessed by comparing the observed mortality rate with the median predicted probability for one-year mortality. Each subject's risk of mortality was predicted from individual baseline data using the Meta-Analysis Global Group in Chronic HF (MAGGIC) prognostic model. Results: A total of 87 patients had undergone successful device implantation for the treatment of HFrEF (53%) and HFpEF (47%). Sixty patients had a complete twelve-month follow-up. The median follow-up was 351 days (interquartile range [IQR] 202–370). A total of six (7%) patients died during follow-up (8.6 deaths per 100 patient-years; 95% confidence interval [CI] 2.7 to 15.5), all of which had HFrEF. The median predicted mortality rate for the overall study population was 12.2 deaths per 100 patient-years (95% CI 10.2 to 14.7). While the observed mortality rate (0 deaths per 100 patient-years) was significantly lower than the median predicted mortality rate (9.3 deaths per 100 patient-years; 95% CI 8.4 to 11.1) in patients with HFpEF (−9.3 deaths per 100 patient-years; 95% CI −11.1 to −8.4), there was no difference in patients with HFrEF (−3.6 deaths per 100 patient-years; 95% CI −9.5 to 3.0) (Figure 1). Four deaths were HF-related deaths (5.7 HF-related deaths per 100 patient-years; 95% CI 1.4 to 11.9; 10.8 HF-related deaths per 100 patient-years; 95% CI 2.5 to 23.1 in the HFrEF subgroup). Conclusion: In patients with HFpEF, the mortality rate following atrial flow regulator implantation was lower than the predicted mortality rate. These findings need to be confirmed by larger randomised, controlled trials. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Occlutech International AB